Pengaruh Pertumbuhan Bibit Mucuna Bracteata di Media Tanaman Top Soil dan Kompos Kotoran Sapi Pada Wadah Bambo - Toto Suryanto; Arif Kurniawan (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2024)
This research aims to determine the percentage of germination and the effect of planting media in bamboo containers on the growth of Mucuna bracteata seedlings. This research was carried out at the Experimental Garden of the Faculty of Agriculture, Borobudur University in June 2024 for 15 days after planting. This research used a descriptive method with treatment comparing top soil planting media with cow dung compost on the growth of Mucuna bracteate seedlings in bamboo containers. This research uses planting media in the form of top soil and cow dung compost. The results of this research show that seed germination is 70% and growth in height (4.57 cm), stem diameter (2.43 mm) and number of leaves (4.28 pieces) on cow dung compost media.